Resposta :
Resposta:
Solução:
Aplicando a Lei dos cossenos, obtemos:
[tex]\sf \displaystyle (F_r)^2 = (F_1)^2 + (F_2)^2 +2 \cdot F_1 \cdot F_2 \cdot \cos{\theta}[/tex]
[tex]\sf \displaystyle (F_r)^2 = 5^2 + (12)^2 +2 \cdot 5 \cdot 12 \cdot \cos{60^\circ}[/tex]
[tex]\sf \displaystyle (F_r)^2 =25+ 144 +120 \cdot0,5[/tex]
[tex]\sf \displaystyle (F_r)^2 = 169 +60[/tex]
[tex]\sf \displaystyle (F_r)^2 = 229[/tex]
[tex]\boxed{ \boxed { \boldsymbol{ \sf \displaystyle F_r =\sqrt{229}\: N }}} \quad \gets \text{\sf \textbf{Resposta } }[/tex]
Alternativa correta é o item A.
Explicação: